Estimating the prevalence of six common respiratory viral infections in Zhangzhou, China using nasopharyngeal swabs in adults and throat swabs in Children - Yuanjun Zeng; Guowei Wang; Huicong Yang; Hongmei Li; Yueli Guo; Huili Liu; Xiaojun Xu; Chunbin Zhang (Scientific Reports)
Abstract Acute respiratory viral infections are a major public health concern worldwide, causing significant morbidity and economic burden. Understanding the epidemiological characteristics of these infections is crucial for effective control and prevention measures. The study aimed to investigate the epidemiology of six common respiratory viral infections in Zhangzhou, Fujian Province, China. Clinical and demographic information, along with throat swabs from children and nasopharyngeal swabs from adults, were collected from 19,523 patients from Jan 2023 to Aug 2024 in Zhangzhou, Fujian Province, China. Multiplex RT-PCR was performed to detected six respiratory viral pathogens. At least one virus was detected in 6911 cases, the positivity rate was 35.40%. A total of 440 cases of mixed infection with two or more viruses were detected, and the positivity rate of co-infection was 2.25%. Age-specific analysis revealed that RSV predominantly affected children aged 0–3 years, while FluA had a broader age distribution, with significant incidences in elderly (≥ 60 years old). Seasonal peaks in viral detection were observed in Mar and Jul 2023, as well as Apr 2024. Overall, there was no statistically significant difference in viral detection rates between sexes, with the exception of the 6–14 years age group, where males exhibited a higher rate. Co-infections were more prevalent during the summer months and were particularly common among children aged 1–3 years. The study highlights the distinct age, sex, and seasonal patterns of six common respiratory viral infections in Zhangzhou, China. These findings emphasize the need for targeted age-specific and seasonal public health interventions to effectively prevent and control these infections.